Remarks and clarifications on the type material of Ximenesia encelioides (Verbesina encelioides; Asteraceae, Heliantheae), with a new lectotype designation - Crespo, Manuel B.; Alonso, Mª Ángeles (Phytotaxa, 2016)
In a recent paper, the name Ximenesia encelioides was lectotypified on material conserved at MA. However, the selected “lectotype” includes several fragments collected at three different times, and that herbarium sheet is therefore to be considered to contain three different specimens as defined in Art. 8.2 of the International Code of Nomenclature of algae, fungi and plants. This fact makes that “lectotype” invalid since contrary to Art. 8.1, and hence the previous lectotypification is to be disregarded. Accordingly, a new lectotype is designated for that name, currently accepted as Verbesina encelioides.